A KOHA customization, migration, and training project for the Quezon City Public Library - Corral, Valerie Darl M.; Piquero, Giancarlo M. (2013)
The Quezon City Public Library (QCPL) is the largest public library in Metro Manila and serves nearly 2.679 million residents through its main library located at the back of Quezon City Hall and 21 branch libraries distributed all over the city. As a part of its commitment to continue to provide its users a wide variety of quality programs and services, the QCPL is upgrading its integrated library system (ILS)-- primarily to enhance its online public access catalog (OPAC) and automate select processes involved in everyday library work.